Persepsi Kader Muslimah Wahdah terhadap Akad Syirkah dan Implementasinya dalam Perspektif Fikih Muamalat - Rahmayani Rahmayani; Iskandar Iskandar; Misriani Misriani (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The form of business organization in which two or more people work together in terms of funds, entrepreneurship, skills and good intentions to run a business, is categorized by the jurists as a form of syirkah. However, in practice, we often face problems that can harm various parties, including Muslim women entrepreneurs in Wahdah Makassar. The aim of the research is to determine the perception of Muslim Wahdah cadres regarding the syirkah contract and how it is implemented. The formulation of the problem raised is: first, what is the perception of Wahdah Muslimah cadres regarding the syirkah contract; second, how is the implementation of the syirkah contract among Wahdah Muslim women from the perspective of muamalat fiqh. The method used is a mixed methods method. Apart from that, it also uses an explanatory sequential design approach (explanatory sequential design). The results can be concluded as follows: first, the results of the quantitative descriptive analysis show a figure of 98.1%, which means that the perception of Muslimah Wahdah Makassar cadres is in the positive category, with an average score from respondents of 80.19 points. secondly, the implementation of the syirkah contract among Muslim Wahdah entrepreneurs is also positive, looking at the analysis of the results of the interviews conducted, showing that they understand quite well in carrying out the syirkah contract in accordance with muamalat fiqh. According to them, the syirkah contract is a contract that is prescribed by law, so complete knowledge is needed to carry out this system in accordance with muamalat fiqh.